Pengolahan Limbah Tongkol Jagung Menjadi Asap Cair dengan Metode Pirolisis Lambat - Syahrir, Muallim; Mahyati, Mahyati (Politeknik Negeri Ujung Pandang, 2019)
The purpose of this study was to determine the temperature, time and the optimum size of the pyrolysis process to yield liquid smoke, and to know the grade of liquid smoke. Pyrolysis process were done by varying the temperature 350oC, 400oC, 450oC, 500oC, the time variation of 30 minutes, 60 minutes, 90 minutes, 120 minutes, 150 minutes, 180 minutes and a variety of fine size (3/8 inch), medium (1 inch), coarse (1.5 inches), after the analysis of pH, specific gravity, acid tertitrasi and total phenol content analysis. Liquid smoke that optimum results are calculated to determine whether the economic feasibility of this research can be continued at the industrial stage. The research showed the optimum temperature of 400oC at a yield of 45.5%, the optimum time of 120 minutes resulted in a yield of 46% and smoother optimum size at a yield of 47%. Total acid is between 6.8054% - 7.2746%, pH between 1.8 to 1.9 with phenol levels between 3.4456% - 4% in 1569 to produce liquid smoke to grade 4.